MODIFIKASI SISTEM ERETAN PADA EMCO COMPACT 5-PC CNC LATHE - Pakasi, Christian Jacob; Lumintang, Romels; Rondonuwu, Irvan; Punuhsingon, Charles (Jurnal Poros Teknik Mesin UNSRAT, 2024)
The EMCO Compact 5-PC CNC Lathe engine made in Austria in the laboratory majoring in Mechanical Engineering, Sam Ratulangi University has not been operating due to the use and maintenance of machines that have been lasted for years so that they are not maintained and cannot be operated anymore. In order to be operated again, the machine needs to be repaired and modified. The purpose of this study is the modification of the eretan system in the EMCO Compact 5-PC CNC Lathe by adding a belt transmission system and calibrateing the motor stepper using a computer, so that a more precise product can be produced. Modification of the EMCO Compact 5-Pc CNC Lathe eretan system has been successful. The Modification Process of EMCO Compact 5-Pc CNC Lathe carried out is the replacement of old components with new components and assembling the grade system components based on the CAD image that has been created. Then the machine is connected to a computer/laptop to calibrate and adjust the speed of the stepper motor on the X axis, Y axis, and X axis through the GRBL Controller Software so that the resulting movements are the same as those programmed. Keywords: Modification, CNC Lathe, CAD, Calibration, Stepper Motor, GRBL, Arduino Microcontroller